High Performance Computing 8th CCF Conference, HPC 2012, Zhangjiajie, China, October 29-31, 2012. Revised Selected Papers - Zhang, Yunquan; Li, Kenli; Xiao, Zheng (Communications in Computer and Information Science, 2013)
This book constitutes the refereed proceedings of the National Annual Conference on High Performance Computing, HPC 2012, held in Zhangjiajie, China, in October 2012. The 14 revised full papers presented were carefully reviewed and selected from 260 submissions. The papers address issues such as parallel architecture, GPU computing, resource scheduling, parallel algorithm, and performance evaluation.